ONLINE – MERGE – OFFLINE (OMO) CLASSROOM MODEL AS INNOVATION TO IMPROVE STUDENTS’ MASTERY LEVEL AND ATTITUDE IN TEACHING BALANCING CHEMICAL EQUATION - Prof. Resty C. Samosa; John Glenn C. Maylas; Gregor L. Macalam (Scholar Express Journal, 2021)
This study evaluated the effectiveness of online – merge – offline (OMO) classroom model as innovation to improve students’ mastery level and attitude in teaching balancing chemical equation. The study determines level of mastery and attitude of the students towards the utilization of the Online – Merge – Offline (OMO) Classroom Model in teaching Balancing Chemical Equation. In juxtaposition, the study tests significant difference that exists between the pre-test and post-test results of using Online – Merge – Offline (OMO) Classroom Model in teaching Balancing Chemical Equation. In addition, the researchers made used of validated pretest-posttest and attitude surveyquestionnaire as the primary tools of the study. The findings showed that the students showed a closely approximating mastery as exposed to online – merge – offline (OMO) classroom model had a positive effect on the teaching balancing chemical equation. Affirmatively, it is evident have positive effect on the teaching balancing chemical equation among Grade 9 students as evidenced by the significantly greater mean in the posttest than in the pretest. There was significant difference in the pretest and posttest score of students in the utilization of online – merge – offline (OMO) classroom model had a positive effect on the teaching balancing chemical equation. Engagingly, the students have positive attitude in learning balancing equation as exposed to online – merge – offline (OMO) classroom model. From these findings it is clear pathways for prospective use online-merge-offline (OMO) to other educational institution in the Philippines to integrate towards its vision of educating for the best
Keywords: Attitude; balancing chemical equation; innovation; online